Bibliometric Analysis: Publish or Perish and VOSviewer for Research Trends on Online Violence (2023–2025) - Rachmawati, Indriyana; Sari, Widya Juwita; Mumpuni, Sesya Dias (citeus, 2025)
Cases of online violence have become increasingly widespread since the end of the COVID-19 pandemic, during which individuals began to grow dependent on the digital world. The digital realm has become a fundamental aspect of human life, bringing with it new forms of online violence. Online violence such as threats, hate speech, harassment, and bullying has emerged as a new weapon to control, isolate, and even torment affected victims. However, only a small body of literature has explored the changing nature of online violence following COVID-19. This study aims to review the literature on patterns of online violence post-pandemic, focusing on the years 2023–2025, and to provide recommendations for future research. Bibliometric analysis using VOSviewer was selected to map the patterns of online violence studies published between 2023 and 2025, covering sources from both Scopus and Google Scholar. The findings show that since the end of the COVID-19 pandemic, patterns of online violence have become closely linked to gender, more specifically to violence against women and domestic violence.